TANTANGAN KETERWAKILAN PEREMPUAN DALAM POLITIK FORMAL - Marsyifa Novia Fauziah; Mochamad Faizal Rizki; Rachmat Ramdani (Jurnal Ilmu Pemerintahan Widya Praja, 2023)
Research on the challenges of women's representation in formal politics discusses the process by which Indonesian women have fought in politics to date. In addition, this paper also dissects the factors considered to be the reasons why women can occupy the top leadership both in the executive and legislative realms or as regents/mayors/governors and their representatives. These factors are political costs, supporting parties and family relations. This study was compiled using descriptive qualitative research methods with data collection techniques using literature review. And the results of this study say that political costs in Indonesia depend on the region, population and availability of natural resources in each area. The bearer party as a medium for voting and family relations as a way to communicate and form personal branding quickly.